Influence of “third age” person’s education on cognitive aging and psychological well-being - Belovol, Elena; Elena Shurupova (European Journal of Social Science Education and Research, 2018)
. Influence of standard regular education of elderly adults (aged 55+) on psychological well being and cognitive aging is studied. The hypothesis that education can slow-down the process of cognitive aging has been verified. By the example of longitudinal study, the dynamics of worry domains, their content as well as cognitive functioning improvement have been studied.